CARL SPITTELER A STOSUNKI POLSKO-ROSYJSKIE W DRUGIEJ POŁOWIE XIX WIEKU - Zieliński, Jan (Colloquia Litteraria, 2019)
“Carl Spitteler and Polish-Russian Relationships in the Second Half of the Nineteenth century” This paper deals with Carl Spitteler’s opinions, still not researched and descri- bed, about Polish-Russian relationships in the second half of the nineteenth century, it focuses on the issues of the Russification of former Polish territo- ries. Spitteler had an opportunity to get acquainted in depth both with Russia and the Kingdom of Poland The author reaches interesting conclusions from close reading of a writer who received the Nobel Prize for Literature in 1919.